Problems of providing medical care to children of Ukraine as a result of russian aggression - O.P. Volosovets; O.V. Vyhovska; S.P. Kryvopustov; O.V. Mozyrska; O.V. Yemets; A.O. Volosovets; Wojciech Feleszko (Zaslavsky O.Yu., 2023)
Background. The russian aggression in Ukraine has caused numerous casualties among civilians, including children. Military actions lead directly or indirectly to increased morbidity in adults and children and to chronic stress, especially in children. The purpose of this research was to analyze the problems of providing medical assistance to the children of Ukraine who are suffering from the russian invasion. Materials and methods. We have used the official statistical and own data for 2022-2023. Results. Currently, more than 7.5 million Ukrainian children are suffering from the war, not only due to physical injuries but also violations of their mental and psycho-emotional state. A special problem for Ukrainian paediatricians at the beginning of 2023 was an increase in the incidence of acute respiratory diseases, COVID-19 and stress disorders in children due to a shortage of medical personnel and infrastructure. Also, in conditions of limited access to medical care and medicines, it is necessary to pay attention to chronic diseases, in particular, asthma and other allergic diseases. Paediatricians from the departments of the Bogomolets National Medical University provided voluntary assistance to children in frontline regions. Conclusions. In the new conditions of warfare, where civilians and life support infrastructure have become the target of armed attacks, children have become the most vulnerable group. The issues of restoration of full medical care for children, including emergency and urgent care, provision with doctors of certain paediatric specialties, full supply of medicines and medical devices, and restoration of destroyed medical infrastructure remain extremely relevant to the health system in the frontline and liberated areas.